Bendix Gas Chromatograph and Mass Spectrometer - Bendix Corporation (1960)
Series of photographs depicting the Bendix Corporation Gas Chromatograph 2500 and Time-of-Flight Mass Spectrometer with a male technician. Assorted control panels are visible in the photograph, including an isothermal controller, electrometer, and temperature programmer. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Gas chromatography; Bendix Corporation; Gas chromatography--Instruments; Mass spectrometers